Polityka informacyjna urzędów centralnych w Polsce na przykładzie wykorzystania internetowych kanałów przekazu informacji - Szczegielniak, Michał (Polityka i Społeczeństwo, 2020)
The aim of this paper is to analyze the information policy of selected central offices on the Internet. In the first part of the article the author defines the nature of information policy. Then the author intends to verify the following thesis: the central offices do not conduct a sufficiently effective information policy. This is due to the lack of systematic action, improper preparation of the content of the messages and the inability to cater to the needs of people with disabilities. The author answers the following research questions: whether the actions taken by the audited offices are in line with a specified strategy or just perform ad hoc actions; whether the information provided is written in intelligible, understandable language and if it is accessible to people with disabilities. Particular attention will be given to the content available on the Internet, in particular on the websites of central offices.